Breeding Potential of Exotic Maize Populations to Improve an Elite Chinese Hybrid. (1st November 2013) - Yong, Hongjun; Li, Mingshun; Li, Xin; Zhang, Xiaocong; Tie, Shuanggui; Meng, Zhaodong; Zhang, Degui; Weng, Jianfeng; Hao, Zhuanfang; Ci, Xiaoke; Li, Xinhai; Zhang, Shihuang
Abstract : Introgression of favorable alleles from exotic maize ( Zea mays L.) germplasm can broaden the narrow genetic base of available temperate germplasm. Development of maize hybrids for the Yellow and Huai river valleys in the Corn Belt of China has always been hampered by the lack of favorable alleles for improving maize yield and quality. Twenty exotic populations from CIMMYT and the United States were evaluated to identify alleles for improving a widely cultivated hybrid, Zheng 58 × Chang 7‐2, which represents the predominant heterotic group, PA × Sipingtou. Sixty‐three genotypes, comprising 20 populations, two inbred lines (Zheng 58 and Chang 7‐2), a single‐cross hybrid (Zheng 58 × Chang 7‐2), and 40 inbred × population crosses between the parental inbreds and the CIMMYT and U.S. populations were evaluated for grain yield, test weight, and ear height. Several populations from CIMMYT and the United States were identified as potential sources of favorable alleles for traits lacking in the elite hybrid, Zheng 58 × Chang 7‐2, for each trait evaluated. Two exotic populations, Pop 49 and Stay green‐yellow, were the most outstanding because they possessed favorable alleles for several traits that were not present in the target hybrid evaluated. These results demonstrate that the exotic populations evaluated in this study represent sources of useful genetic variability with good potential for improving Chinese elite germplasm.